Characterization of sulfoxaflor resistance in the brown planthopper, Nilaparvata lugens (Stål). Issue 6 (7th January 2019) - Liao, Xun; Jin, Ruoheng; Zhang, Xiaolei; Ali, Ehsan; Mao, Kaikai; Xu, Pengfei; Li, Jianhong; Wan, Hu
Abstract: BACKGROUND: Sulfoxaflor is a new insecticide for controlling Nilaparvata lugens in the field. This study was conducted to investigate the risk of resistance development, the cross‐resistance spectrum and the mechanisms of sulfoxaflor resistance in N. lugens . RESULTS: A sulfoxaflor‐resistant strain was obtained from a field population by successive selection with sulfoxaflor for 39 generations in the laboratory. Sulfoxaflor‐resistant populations showed significant levels of cross‐resistance to dinotefuran, nitenpyram, thiamethoxam, clothianidin, imidacloprid and cycloxaprid. However, they exhibited only minor or no cross‐resistance to isoprocarb, etofenprox, chlorpyrifos, triflumezopyrim and buprofezin. Sulfoxaflor was synergized by the inhibitor piperonyl butoxide (PBO) in the sulfoxaflor‐resistant strain (SFX‐SEL) with 2.69‐fold relative synergistic ratios compared with the unselected strain (UNSEL). Compared with UNSEL, the P450 enzyme activity of SFX‐SEL was increased 3.50 times, and eight P450 genes were upregulated more than 2.0‐fold in SFX‐SEL. RNAi reduced the expression of CYP6ER1 (36.87‐fold change) and significantly enhanced the susceptibility of SFX‐SEL to sulfoxaflor. CONCLUSION: Resistance development and cross‐resistance risk of sulfoxaflor‐resistance in N. lugens is evident. The enhanced detoxification of P450 enzymes caused by upregulation of several P450 genes is considered to be the metabolic resistance mechanism. These results suggest that CYP6ER1 might play an important role in sulfoxaflor resistance in N. lugens . © 2018 Society of Chemical Industry Abstract : Sulfoxaflor‐resistant populations showed significant levels of cross‐resistance to all tested neonicotinoid insecticides. The enhanced detoxification of P450 enzymes caused by upregulation of several P450 genes is considered to be the metabolic resistance mechanism.